Ответ:
[tex]1.m - m + b = b \\ x - x + c = c\\ 2.a + a - 7 = 2a - 7 \\ t - t + 1 = 1 \\ 3.b + 3 - b - 9 = - 6 \\ a + 2 - a - 9 = - 7[/tex]
Пошаговое объяснение: cумма противоположных равна 0 ( а и -а)
1)m-(m -b)=m-m+b=b 1)x+(-x+c)=x-x+c=c
2)a+(-a-7)=a-a-7= -7 2) t-(t-1)=t -t +1=1
3)(b+3)-(b+9)=b+3-b-9= -6 3)(a+2)-(a+9)=a+2-a-9=-7
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
[tex]1.m - m + b = b \\ x - x + c = c\\ 2.a + a - 7 = 2a - 7 \\ t - t + 1 = 1 \\ 3.b + 3 - b - 9 = - 6 \\ a + 2 - a - 9 = - 7[/tex]
Ответ:
Пошаговое объяснение: cумма противоположных равна 0 ( а и -а)
1)m-(m -b)=m-m+b=b 1)x+(-x+c)=x-x+c=c
2)a+(-a-7)=a-a-7= -7 2) t-(t-1)=t -t +1=1
3)(b+3)-(b+9)=b+3-b-9= -6 3)(a+2)-(a+9)=a+2-a-9=-7